c.1 - Ocampo, Jose Antonio (ed.) (Hyderabad, 2007)
In 2000 the UN pledged to halve world poverty by 2015 as part of the Millennium Development Goals (MDGs), but progress has been elusive, and consensus difficult to achieve. These papers reveal disparate problems faced by the UN in developing a coherent Development Agenda, from the complex effects of trade and finance liberalization to the damaging realities of development aid, itself a central pillar of the MDGs. The unifying theme is one of economic and social integration, and an emphasis on long-term strategic investment in education, health and infrastructure. By challenging mainstream economic thought, this book is required reading for students, academics and activists wanting to engage in the debate, and help the MDGs reach a positive conclusion.
Keywords: Economic policy